Simulation of the Spindle Coupled Multi-Axial Loading Fatigue Test of a Rear Axle - Dong, Z.; Wang, X.; Lou, W.; Huang, Y.; Zhong, M.; Fan, H.; Peng, L. (Проблемы прочности, 2017)
This study aims to establish a practical method for simulating the spindle coupled multi-axis loading fatigue test of a rear axle. A dynamic finite-element model of the rear axle was constructed and validated using a static calibration test. Based on the theory and methodology of the Schenck ITFC system, a simulation process was devised which includes system identification, calculation of the input loading signals for the finite-element model, calculation of the response stress signals based on this model, calculation of the response strain signals from the corresponding stress signals, and finally, a comparison of the desired and achieved signals. The corresponding data processing programs were made using Matlab, ensuring their easy reproducibility. The desired signals were measured on the Hainan proving ground for a duration of 2441.216 s, using strain gauges and rosettes placed in important stress-prone locations of the rear axle. The results indicate that the desired signals can be reproduced comparatively accurately, ensuring that the strain distribution of the rear axle in the field can be reasonably predicted.